2021
DOI: 10.1111/gcb.15775
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in GPP/SIF ratios and their climatic determinants across the Northern Hemisphere

Abstract: Satellite-derived sun-induced chlorophyll fluorescence (SIF) has been increasingly used for estimating gross primary production (GPP). However, the relationship between SIF and GPP has not been well defined, impeding the translation of satellite observed SIF to GPP. Previous studies have generally assumed a linear relationship between SIF and GPP at daily and longer time scales, but support for this assumption is lacking. Here, we used the GPP/SIF ratio to investigate seasonal variations in the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 65 publications
0
39
2
Order By: Relevance
“…where slope is the change in SIF or GPP per year, x i is the value of SIF or GPP, n is the total number of years under investigation (n =18), and t i denotes the year from 2001 to 2018 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A positive (negative) slope value represents increase (decrease) in SIF or GPP.…”
Section: Trend Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…where slope is the change in SIF or GPP per year, x i is the value of SIF or GPP, n is the total number of years under investigation (n =18), and t i denotes the year from 2001 to 2018 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A positive (negative) slope value represents increase (decrease) in SIF or GPP.…”
Section: Trend Analysismentioning
confidence: 99%
“…The effects of meteorological factors on SIF and GPP are complicated. In the literature, there are lot of studies on analyzing the relationship between SIF/GPP and temperature, precipitation, or radiation at different scales (Chen et al 2021;Liu et al 2018;Xu et al 2021). SIF and GPP may be used as measures to study vegetation growth (Magney et al 2019;Guanter et al 2014) To provide a holist picture of wind speed effects on plants, SIF and GPP are used to evaluate wind effects on the growth of global vegetations in this work based on the Global Land Data Assimilation System (GLDAS)data, SIF and GPP data, and the Terra and Aqua combined Moderate Resolution Imaging Spectroradiometer (MODIS) Land Cover Climate Modeling Grid (CMG) (MCD12C1) Version 6 data product.…”
Section: Introductionmentioning
confidence: 99%
“…The primary climate variables used in this study are shown in Table 1, either directly from this product or calculated from the variables provided by this product. It has been demonstrated that climatic circumstances might influence vegetation growth [38,[56][57][58][59], thus the climate factors for the current month, the previous month, and the previous two months were considered as input variables for the model.…”
Section: Climatic Datamentioning
confidence: 99%
“…This finding provides new insight for estimating ecosystem-scale GPP and encourages us to utilize SIF in carbon cycle research as a reliable proxy for GPP. However, as SIF products have only been available since 2000, the reasons for the variations in the relationship between SIF and GPP over time and space need to be clarified [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation